Dwie brązowe siekierki z okolic Pułtuska - Affelski, Jakub (Acta Universitatis Lodziensis. Folia Archaeologica, 2011)
The presented article aims at discussing the discovery of two types of axes made of bronze, coming from the northern Masovia area (the neighbourhood of Pułtusk). The first specimen is a bronze axe with edges. The artifact has typical characteristics, a rounded butt, thick low edges, weakly bended sides, and an open arched blade. Despite the relatively untypical morphometric features, the specimen was ascribed to the collection of axes with edges of the Grodnica type. As far as the chronology is concerned, the specimen is dated to phase BrC. The other specimen is a bronze socketed axe. The artifact is a classic example of a “Lusatian” type axe. A detailed analysis shows that in this case it is the Kotowo type that is concerned. It is characteristic of a collar-like mouth of the socket, a slight narrowing in the half-length and a decoration in the form of vertical ribs placed between arched edges. The character and the area of its occurrence suggest that the axe from Pu³tusk probably arrived from the western area of the Lusatian culture to the border area occupied by the North-Masovian or Masovian-Podlasie groups. In respect of chronology the axe should be placed in the decline phase of the Bronze Age (HaB2–HaB3). Both types of bronze axes are exotic to northern Masovia because their provenance should be connected with the western areas of Poland.